(untitled) (Research Nepal Journal of Development Studies, 2023)
Education is a basic human right. The Constitution of Nepal has specified education as a citizen’s right. Education is the basic foundation of the development of any country. Therefore, it is the duty of the government to provide quality education to all its citizens. To this end, the Government of Nepal has adopted the policy of "Education for All’ and provided free education up to the secondary school level in community-managed schools. Internet based library method has been applied. It is a Review of the existing status, government policy, NTA policy, and AEPC strategy on the promotion of energy services and internet services were conducted to prepare the action plan. In conclusion, Government of Nepal has realized the importance of the computer education and use of science and technology, information technology, digitization of the curriculum through of use of applications and modern teaching methodology.